Kinetic and thermodynamic modelling of thermal decomposition of bitumen under high pressure enhanced with simulated annealing and artificial intelligence. (14th May 2021) - Alade, Olalekan; Gang, Lei; Tariq, Zeeshan; Mahmoud, Mohamed; Al Shehri, Dhafer; Sultan, Abdullah; Al‐Ramadhan, Ammar; Mokheimer, Esmail
Abstract: Thermogravimetric analysis (TGA) of energy resources including bitumen provides kinetic parameters, which can be applied in design and simulation of processes for thermal recovery and conversion. In this investigation, pressurized non‐isothermal decomposition of bitumen under inert environment has been studied. The kinetic parameters were calculated at different pressures (0.1, 0.5, and 1 MPa) and heating rates (10, 20, and 30°C/min) using the differential method. The parameters were later optimized using simulated annealing (SA) optimization algorithm. The results were subsequently validated by comparing the predicted conversion (α) with those of artificial neural network (ANN). Thermodynamic parameters (enthalpy, entropy, and Gibb's free energy) were also calculated using the optimized kinetic parameters. The TGA results show that weight loss and thermal conversion decreased as the total pressure increased from 0.1–1 MPa, at all heating rates. Conversely, the thermal conversion rate ( dα/dT ) was observed to first decrease with increasing pressure (0.1–1 MPa) within the low temperature oxidation (LTO) and fuel deposition (FD) regions. In contrast, it increased with increasing total pressure within the high temperature oxidation (HTO) region. Furthermore, it was observed that the activation energy ( E a ) increased with increasing pressures at all heating rates, while the frequency factor ( A ) was independent of the pressure or the heating rates. In addition, the thermodynamic parameters tend to increase with increasing pressure. Ultimately, the results established that the SA algorithm could be used to enhance the performance of the differential modelling method in calculating kinetic parameters and predicting the conversion. Abstract : Modelling high pressure thermogravimetric analysis (TGA) of bitumen.